Impact of Intellectual Capital on Stock Price with Financial Performance as an Intermediating Variable: Special Reference to Listed Companies in CSE Sri Lanka. - Tharshiga, P. (International Institute of Academic Research & Publications, 2023)
The modern business world is constantly changing. Consequently, companies must face and fight to change competition conditions by adapting appropriately. In this respect, the organization believes that only tangible assets are insufficient to compete with competitors. Therefore, the present study attempts to analyze the impact of intellectual capital (IC) on stock prices with financial performance as an intervening variable. For the study, data were collected using a random sampling method from 2015 to 2022. Descriptive calculations, multiple regression appraisals, and the Sobel examination were utilized to find the results. The analyzed results indicated that IC has a significant impact on the financial performance of the companies. However, the researcher does not have strong statistical evidence to conclude that IC significantly affects the stock price, with financial performance as an intervening variable. Only physical capital significantly impacts the stock price when ROE is used as an intervening variable. The results are significant for all the stakeholders, especially for investors in making their investment decisions on the company shares. Companies could also realize the importance of IC to obtain competitive advantages and face market challenges and competition. Some theories explain that positive relationships exist between IC, financial performance, and stock prices of the companies. There will be a gap when the study's findings are compared with the theoretical conclusions. For the problem, researchers believe that the country's conditions may moderate the relationship between IC, financial performance, and companies' stock prices. Therefore, the researcher suggested that future researchers conduct the same problem with different samples and draw fruitful conclusions and recommendations for the relevant stakeholders.
Keywords: Intellectual Capital; Return on Asset; Return on Equity; Intermediating Variable; Stock Prices